Transformation of Terraces with Irrigation Systems: Profitability and Water Savings in Potato Crop (Solanum tuberosum L.) - Poma Chamana, Russell (2025)
MDPI stays neutral with regard to jurisdictional claims in published maps and institutional affiliations.